An efficient Imprecise 4:2 Compressor Using Gate Diffusion Input Supplemented with Dynamic Threshold - Forouzan Bahrami; Nabiollah Shiri; Farshad Pesaran (مهندسی مخابرات جنوب)
Approximate computing is a new design concept that causes a trade-off between circuitry performance and accuracy. The approximate circuits are more useful in error-resilient applications, like image processing. This paper introduces a new imprecise 4:2 compressor with 12 transistors. The presented compressor exhibits low power consumption and provides full-swing outputs, due to the utilization of gate diffusion input and dynamic threshold techniques. The implementation of this compressor using a 16 nm carbon nanotube field-effect transistor (CNTFET) technology yields a minimum area. According to the simulation results, the suggested imprecise 4:2 compressor shows a significant reduction in power consumption and power-delay-product (PDP) compared to the precise 4:2 compressor, with a reduction of 95.18% and 95.27%, respectively. Also, the compressor is evaluated regarding the approximate figure of merits like error rate, mean error distance, and normalized mean error distance. The simulation results affirm the priority of the suggested circuit, especially in digital signal processing.